Long-term hippocampal glutamate synapse and astrocyte dysfunctions underlying the altered phenotype induced by adolescent THC treatment in male rats. (September 2016) - Zamberletti, Erica; Gabaglio, Marina; Grilli, Massimo; Prini, Pamela; Catanese, Alberto; Pittaluga, Anna; Marchi, Mario; Rubino, Tiziana; Parolaro, Daniela
Graphical abstract: Abstract: Cannabis use has been frequently associated with sex-dependent effects on brain and behavior. We previously demonstrated that adult female rats exposed to delta-9-tetrahydrocannabinol (THC) during adolescence develop long-term alterations in cognitive performances and emotional reactivity, whereas preliminary evidence suggests the presence of a different phenotype in male rats. To thoroughly depict the behavioral phenotype induced by adolescent THC exposure in male rats, we treated adolescent animals with increasing doses of THC twice a day (PND 35⿿45) and, at adulthood, we performed a battery of behavioral tests to measure affective- and psychotic-like symptoms as well as cognition. Poorer memory performance and psychotic-like behaviors were present after adolescent THC treatment in male rats, without alterations in the emotional component. At cellular level, the expression of the NMDA receptor subunit, GluN2B, as well as the levels of the AMPA subunits, GluA1 and GluA2, were significantly increased in hippocampal post-synaptic fractions from THC-exposed rats compared to controls. Furthermore, increases in the levels of the pre-synaptic marker, synaptophysin, and the post-synaptic marker, PSD95, were also present. Interestingly, KCl-induced [ 3 H]D-ASP release from hippocampal synaptosomes, but not gliosomes, was significantly enhanced in THC-treated rats compared to controls. Moreover, in the same brain region, adolescent THC treatment also resulted in a persistent neuroinflammatory state, characterized by increased expression of the astrocyte marker, GFAP, increased levels of the pro-inflammatory markers, TNF-α, iNOS and COX-2, as well as a concomitant reduction of the anti-inflammatory cytokine, IL-10. Notably, none of these alterations was observed in the prefrontal cortex (PFC). Together with our previous findings in females, these data suggest that the sex-dependent detrimental effects induced by adolescent THC exposure on adult behavior may rely on its ability to trigger different region-dependent changes in glutamate synapse and glial cells. The phenotype observed in males is mainly associated with marked dysregulations in the hippocampus, whereas the prevalence of alterations in the emotional sphere in females is associated with profound changes in the PFC.